MULTIDISCIPLINARY STUDY OF THE LEVEL OF AVAILABILITY OF MEDICINES FOR CANCER PATIENTS BASED ON THE PRINCIPLES OF PHARMACEUTICAL LAW, EVIDENCE-BASED PHARMACY, CLINICAL PHARMACY, FORENSIC PHARMACY, AND THE ORGANIZATION OF A PHARMACEUTICAL CASE - Shapovalov Валерій (Actual Problems of Medicine and Pharmacy, 2023)
A multidisciplinary study of the level of availability of drugs of different clinical and pharmacological, classification and legal, nomenclature and legal groups of the circulation of cancer patients was conducted. The statistics of oncological morbidity was analyzed on a retrospective scale using the example of rural areas of the Kharkiv region and Ukraine. The state of pharmaceutical supply of cancer patients with drugs is considered. The prices of drugs for pharmacotherapy of cancer patients in eighteen high-income countries of the world and in Ukraine were compared. The need to improve mechanisms of prevention, screening, early detection of tumors, introduction of new medical technologies, provision of physical and psychological support to patients and improvement of their quality of life is justified. Forensic pharmaceutical practice regarding the violation of the rights of cancer patients in the process of providing analgesic pharmacotherapy was analyzed. Normative initiatives have been developed to increase the level of availability of drugs of clinical and pharmacological, classification and legal, nomenclature and legal groups for cancer patients in Ukraine based on a multidisciplinary approach.